Bioactıve Glass-Polymer Nanocomposites for Bone Tıssue Regeneration Applicatıons: A Revıew - Erol-Taygun, Melek; Ünalan, Irem; Idris, Maizlinda Izwana Binti; Mano, João F.; Boccaccini, Aldo R. (Advanced Engineering Materials, 2019)
Nanosized bioactive glass (NBG) particles are attractive materials for bone repair because of their ability to enhance bone formation and to chemically bond to the surrounding bone tissue. In recent years, composites of biopolymers and NBG particles have been developed for bone tissue engineering due to their increased bioactivity, biocompatibility, and biodegradability. In this paper, the authors review current knowledge regarding polymer/NBG composites, including nanoscale-related features and ion-release effects of bioactive glass (BG) with respect to osteogenic and angiogenic responses in vivo and in vitro; the authors also focus on the techniques used to fabricate these nanocomposites. Additionally, this review discusses recent developments in the use of nanocomposites for tissue engineering and represents a literature update, as well an expansion, of previously published articles on this topic.
CRIS-Team Scopus Importer:2019-07-16
Keywords: angiogenesis; bioactive glasses; bone tissue engineering; composites; ion release; nanoparticles; osteogenesis; scaffolds